Impacts of Stony Coral Tissue Loss Disease (SCTLD) on Coral Community Structure at an Inshore Patch Reef of the Upper Florida Keys Using Photomosaics - Kolodziej, Graham; Studivan, Michael S.; Gleason, Arthur C. R.; Langdon, Chris; Enochs, Ian C.; Manzello, Derek P. (Frontiers in Marine Science, 2021)
Since the appearance of stony coral tissue loss disease (SCTLD) on reefs off Miami in 2014, this unprecedented outbreak has spread across the entirety of Florida’s coral reef tract, as well as to many territories throughout the Caribbean. The endemic zone reached the upper Florida Keys by 2016, resulting in partial or complete mortality of coral colonies across numerous species. Disease was first observed at Cheeca Rocks (Islamorada, Florida) in the beginning of 2018, with reports of coral mortality peaking mid-year. The disease was still present at Cheeca Rocks as of March 2021, however to a lesser degree compared to the initial outbreak. Annual monitoring efforts have been ongoing at Cheeca Rocks since 2012, including repeated benthic photomosaics of a 330 m2 survey zone, spanning six replicate sites. As such, a repository of coral community composition data exists for before and after the disease outbreak that was analyzed to assess the impacts of SCTLD on reef communities at an upper Florida Keys inshore reef. Cheeca Rocks is hypothesized to be a resilient reef due to its persistent high coral cover despite its inshore location, which subjects corals to fluctuating water quality and marginal environmental conditions. Coral populations have been shown to recover from bleaching events and heat stress with minimal coral mortality. Though colonies of coral species characterized as highly and moderately susceptible to SCTLD (e.g., Colpophyllia natans, Diploria labyrinthiformis, Pseudodiploria strigosa, Orbicella annularis, and O. faveolata) suffered mortality as a result of the outbreak with an average loss of 16.42% relative cover by species, the overall impacts on coral cover and community structure were relatively low, contributing to a loss of total coral cover of only 1.65%. Comparison of photomosaic data to other studies indicate Cheeca Rocks may not have been affected as severely as other sites on Florida’s coral reef tract, underlying this site’s potential role in coral resilience to stressors including bleaching events, land-based pollution, and disease epizootics.